Optimization of anti-clogging pervious pavement structure based on numerical evaluation. (15th March 2021) - Zhang, Jiong; Xia, Shuang; Hu, Nian; Hao, Wengang; Han, Ruonan; Meng, Bowen; Zhang, Zhongze
Highlights: The anti-clogging performance of various permeable structures is studied by numerical method. The anti-clogging mechanism of double-layer permeable pavement structure are studied. A tubular double-layer permeable structure with good anti-clogging performance is developed. Abstract: Based on numerical simulation methods, the anti-clogging performance of various pervious pavement structures were investigated. Different pavement structure models were built to analyze the effects of different pervious structures, top layer thicknesses and top aggregate gradations on the anti-clogging performance. The results shown that compared with single-layer structure, the double-layer pervious structure has better anti-clogging performance and maintenance efficiency. The most serious clogging of double-layer pervious structure can be hold within 3 mm of the superficial layer where the clogging particles can more easily be cleaned out. Smaller top layer thickness lead to a better anti-clogging performance and maintenance efficiency. And the top layer aggregate size should be selected only considering particle transport or shielding effect, based on the gradation of local clogging particles. In addition, based on the above findings, a new double-layer pervious structure with excellent anti-clogging performance has been developed, including a number of parallel vertical variable diameter tubular channels, the diameter of the upper layer is smaller than that of the lower layer.